Muslim Women’s Politics in Advancing Their Gender Interests: A Case-Study of Nasyiatul Aisyiyah in Indonesia New Order Era - Siti Syamsiyatun (Al-Jami'ah Research Centre, 2007)
This article analyses a strategy of Nasyiatul Aisyiyah, a youth Muslim women organization, in developing its ideology and the importance of gender in the reign of New Order Indonesia (1966-1998). In the name of political stability, the New Order applied a tight political control towards mass-religious based organizations and tried to minimize their militancy by forming new women’s movement organizations such as Dharma Wanita and PKK that are easily controlled by the government. As an Islamic women organization, Nasyiatul Aisyiyah underwent the surveillance practiced by the government via those two bodies; however Nasyiatul Aisyiyah could constantly maintain its entity as an Islamic women organization. In the 1980s when the New Order Regime was predominantly in power, Nasyiatul Aisyiyah held negotiations and adapted to the governmental gender policy to assure the position and the interests of young women.